2014
DOI: 10.1007/s13277-014-2776-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia during routine follow-up may predict relapse in patients with extranodal NK/T cell lymphoma

Abstract: Recently, absolute lymphocyte count (ALC) at diagnosis, as a surrogate marker of host immunity, has been reported to be a prognostic factor for clinical outcomes in extranodal NK/T cell lymphoma (ENKTL). In this retrospective study, we set out to investigate whether ALC at the time of confirmed relapse or at last follow-up is a marker for relapse after chemoradiotherapy in 84 patients with stage I/II ENKTL. Receiver operating characteristics (ROC) curve and area under the curve (AUC) analysis showed that ALC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…ENKL can cause destruction in the involved site because of its highly invasive behavior, which greatly affects patients’ quality of life. In addition, ~ 30–50% patients will relapse after initial treatment within 5 years, and the treatment of relapsed/refractory ENKL remains challenging 3 …”
mentioning
confidence: 99%
“…ENKL can cause destruction in the involved site because of its highly invasive behavior, which greatly affects patients’ quality of life. In addition, ~ 30–50% patients will relapse after initial treatment within 5 years, and the treatment of relapsed/refractory ENKL remains challenging 3 …”
mentioning
confidence: 99%
“…In ENKTL, previous studies of circulating immune cells mainly focused on ALCs, which considered ALCs as a predictor of immune status. The decreasing ALCs as an indicator of pre-existing immune suppression is an unfavorable prognostic index for ENKTL [9,10]. Because of high-level expression of multidrug resistance P-glycoprotein on ENKTL lymphoma cells, pegaspargase-based therapies were given to untreated ENKTL patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have demonstrated that a decreasing absolute lymphocyte counts (ALCs) is an unfavorable prognostic index for ENKTL, while an increasing ALCs is a favorable prognostic index. However, treatment is heterogeneous and many patients received an inferior regimen like anthracycline-containing treatment [9,10]. Data are limited with respect to the role of specific circulating lymphocyte subsets in the progression of ENKTL patients, especially those treated with asparaginase-containing regimens [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymotherapy is also applied in the treatment of Non-Hodgkin lymphomas in combination with various other therapeutic agents (d'Amore et al, 2015;Dreyling et al, 2013;Wang et al, 2015). Of note, type II asparaginases are induced in bacteria under aerobic conditions only and have a highly specific (but not exclusive) asparagine activity while type I arginases are expressed independently of the environmental condition and similarly hydrolyze L-asparagine and L-glutamine (Batool et al, 2016).…”
Section: Asparagine Targeting: An Example Of Clinical Success In Allmentioning
confidence: 99%